An equation is formed of two equal expressions. The solution of the equation √(x+12)=x is x=4.
An equation is formed when two equal expressions are equated together with the help of an equal sign '='.
The solution of the equation √(x+12)=x can be done as,
[tex]\sqrt{x+12} = x\\\\\text{Square both the sides of the equation}\\\\x+12=x^2\\\\x^2-x-12=0\\\\x^2-4x+3x-12=0\\\\x(x-4)+3(x-4)=0\\\\(x-4)(x+3)=0[/tex]
Equate each of the factors with 0,
[tex](x-4)=0\\x=4\\\\(x+3)=0\\x=-3[/tex]
Now, if we substitute the value of x in the equation given, only the value of x as 4 will satisfy the equation.
Thus, the solution of the equation √(x+12)=x is x=4.
Learn more about Equation:
https://brainly.com/question/2263981